2019
DOI: 10.5114/biolsport.2019.79976
|View full text |Cite
|
Sign up to set email alerts
|

The elevation training mask induces modest hypoxaemia but does not affect heart rate variability during cycling in healthy adults

Abstract: This study examined the acute effects of the elevation training mask (ETM) on haemodynamics and heart rate variability (HRV) at rest, during cycling, and during recovery in healthy adults. Fifteen healthy male (N=9) and female (N=6) adults (27.0 ± 1.14 years) completed two trials with the mask (MASK) and without the mask (CON). The 40-minute cycling exercise protocol included 10-minute phases of (1) rest, (2) 50% of VO 2peak cycling, (3) 70% of VO 2peak cycling, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
(31 reference statements)
4
15
1
5
Order By: Relevance
“…Thus, the SIE ARDS session was not perceived as more difficult, which is of great importance for its implementation in regular training in a variety of populations. Similar findings were reported by Jung et al [ 43 ], where RPE did not differ between normal breathing and respiration with ETM during continuous cycling (50 and 70% VO 2 max). Unfortunately, we did not measure other psychological characteristics, such as the sense of pleasure.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the SIE ARDS session was not perceived as more difficult, which is of great importance for its implementation in regular training in a variety of populations. Similar findings were reported by Jung et al [ 43 ], where RPE did not differ between normal breathing and respiration with ETM during continuous cycling (50 and 70% VO 2 max). Unfortunately, we did not measure other psychological characteristics, such as the sense of pleasure.…”
Section: Discussionsupporting
confidence: 91%
“…Table 1 shows the participants' cardiovascular characteristics prior to cycling. These obtained values are comparable with other baseline measures in previous studies [38,39]. Table 2).…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Although it has been reported that respiratory distress is enhanced by respiratory restriction associated with the surgical mask, there is no report examining the effect of the product on the cardiopulmonary function. Indeed, this aspect must be considered when prescribing the appropriate aerobic exercise intensity at the rehabilitation site if it is established that the respiratory restriction associated with the surgical mask affects the cardiopulmonary function (Jung HC et al, 2019). Therefore, this study aimed to evaluate whether cardiopulmonary function and AT vary when surgical masks are worn.…”
Section: Introductionmentioning
confidence: 99%